1991
DOI: 10.1152/ajplung.1991.261.2.l204
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A is opsonin in phagocytosis of herpes simplex virus type 1 by rat alveolar macrophages

Abstract: In the present study we used flow cytometry to investigate the phagocytosis of fluorescein isothiocyanate-labeled herpes simplex virus type 1 (FITC-HSV-1) by rat alveolar macrophages and the effects of surfactant protein A (SP-A) on this process. The phagocytosis of FITC-HSV-1 by alveolar macrophages, which was studied as a model for virus phagocytosis in general, was strongly enhanced in the presence of SP-A. The SP-A-mediated phagocytosis was time and concentration dependent, reaching a maximal level after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
113
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 0 publications
1
113
0
1
Order By: Relevance
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%
“…Many of the collectins have been shown to affect phagocytic function. The possibility that SP-A might modulate phagocyte function has been supported by recent in vitro experiments [10][11][12][13][14][15][16], although little is known about its role in vivo. In addition, recent studies from our laboratory have demonstrated that SP-A can also influence immune cell function by stimulating mitogen-induced proliferation and cytokine production [17,18].…”
mentioning
confidence: 99%
“…We first proposed that SP-A interacted with the glycans of F 2 and enhanced the fusion activity of F protein. It has been reported that SP-A enhanced uptake of HSV [29] and influenza A virus [30] by alveolar macrophages, and a viral and SP-A glyco-conjugate interaction was suggested in these studies. Carbohydrate recognition and opsonization of viruses may be an important role of SP-A in viral clearance.…”
Section: Discussionmentioning
confidence: 61%